Clinical Study of PTAS Therapy for Patients with Ischemia Cerebrovascular Disease Caused by Artery Stenosis - 刘新通 王伟 唐洲平 曾文高 何池忠 王丽娟 卢海克 李昌茂 张雄 王硕 代成波 马贵贤 杨哲贤 马腾云 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
The curative efficacy of percutaneous transluminal angioplasty and stenting（PTAS） in the treatment of patients with ischemia cerebrovascular disease caused by artery stenosis was explored.The clinical data of 111 patients with ischemia cerebrovascular disease receiving PTAS in Guangdong Province General Hospital from Aug.2007 to Nov.2009 were retrospectively analyzed.In total 132 stents were implanted in the 111 patients.The mortality and rate of neural and non-neural complications were assessed perioperatively.Outcomes [including the frequency of transient ischemic attack（TIA）,stroke,or death from vascular diseases） were assessed after operation.NIHSS rating was performed in all cases before and at first week,6th month and 12th month after the operation.The PTAS success rate was 100%.The degree of stenosis was reduced after PTAS.The total complication rate during perioperative period was 15.3%（the rate of neural complications was 3.6%）.Sixty-seven patients were followed up.Three patients（4.48%） developed cerebrovascular events within 1 month,containing one case of TIA,one case of ipsilateral mild stroke and one case of contralateral mild stroke.No severe stroke or death was observed.During a follow-up period of 12 months 7 patients had cerebrovascular events（10.44%）,including 2 cases of ipsilateral TIA（2.99%）,2 cases of ipsilateral mild stroke and 2 cases of contralateral mild stroke（2.99%）,one case of severe stroke（1.49%）.In 13 patients receiving DSA re-examination one year after PTAS,2 patients（15.38%） had in-stent restenosis.NIHSS scores were obviously decreased during a follow-up period as compared with those pre-operation（P〈0.05）.It was concluded that PTAS could significantly alleviate the neural function deficit of the patients with ischemia cerebrovascular disease.The success rate of PTAS was high,and the rate of complications was lower and the clinical outcomes were satisfactory.PTAS is a safe and effective therapeutic method,though the long-term outcomes need further study.